Applying picture walk and read aloud strategies with supporting audio activities to enhance vocabulary mastery of Elementary School Students at SD Negeri 200104 Padangsidimpuan - Aprida Irmayana; Nina Nurbaidah; Kamisah Kamisah; Azril Maulana; Fatimah Junita Nasution; Juni Sharah Lubis; Nia Rahmadani Hasibuan; Riski Tresya; Suci Rahmadini Harahap; Yolanda Vanesa Andrini (CV. Yudhistt Fateeh, 2026)
This community service program (PKM) aims to improve English vocabulary mastery among sixth-grade students at SD Negeri 200104 Padangsidimpuan. The program implemented